2014
DOI: 10.1016/j.ophtha.2013.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Types, and Lifetime Risk of Adult-Onset Strabismus

Abstract: Objective To describe the incidence and types of adult-onset strabismus in a geographically defined population. Design Retrospectively reviewed population-based cohort. Participants All adult (≥19 years of age) residents of Olmsted County, Minnesota diagnosed with new-onset adult strabismus from January 1, 1985, through December 31, 2004. Methods The medical records of all potential cases identified by the resources of the Rochester Epidemiology Project were reviewed. Main Outcome Measures Incidence ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 36 publications
6
80
1
1
Order By: Relevance
“…In a study of the Rochester Epidemiology Project, divergence insufficiency esotropia was present in 10.6% of adult strabismus cases, at a median age of 74 years (range 19–92 years). 3 In the same population, as age increased, the proportion of adult strabismus patients with divergence insufficiency also increased, with a significant age trend for both men and women. 3 …”
Section: Typical Presentationmentioning
confidence: 98%
“…In a study of the Rochester Epidemiology Project, divergence insufficiency esotropia was present in 10.6% of adult strabismus cases, at a median age of 74 years (range 19–92 years). 3 In the same population, as age increased, the proportion of adult strabismus patients with divergence insufficiency also increased, with a significant age trend for both men and women. 3 …”
Section: Typical Presentationmentioning
confidence: 98%
“…A recent epidemiological study found the annual incidence of adult-onset superior oblique palsy to be 6.3 cases per 100,000 people, but significantly higher in men than women (Martinez-Thompson 2014). In children younger than 19 years of age, the annual incidence was 3.4 cases per 100,000 (Tollefson 2006), with 31% of vertical strabismus in children attributed to superior oblique palsy, of equal incidence by gender.…”
Section: Introductionmentioning
confidence: 99%
“…Şaşılık, değerlendirilen yaş grubuna göre değişkenlik göstermekle birlikte, tüm dünyadaki görülme sıklığı %1 ile %5 arasında bildirilmektedir (1,2) . Olguların önemli bir kısmı ezotropya (ET) ve egzotropya (XT) olmak üzere horizontal tip kaymalardır.…”
Section: Introductionunclassified